Resposta :
Resposta:
Solução:
[tex]\sf \displaystyle f(x) = -4x^{2} +100[/tex]
O vértice da parábola:
[tex]\sf \displaystyle x_v=-\dfrac{b}{2a}[/tex]
[tex]\sf \displaystyle x_v=-\dfrac{0}{2\cdot (-4)}[/tex]
[tex]\boldsymbol{ \sf \displaystyle x_v = 0 }[/tex]
[tex]\sf \displaystyle y_v=-\dfrac{\Delta}{4a}\rightarrow-\dfrac{(b^2-4ac)}{4a}[/tex]
[tex]\sf \displaystyle y_v=-\dfrac{\Delta}{4a}\rightarrow-\dfrac{(0^2-4 \cdot (-4)\cdot 100)}{4\cdot (-4)}[/tex]
[tex]\sf \displaystyle y_v=-\dfrac{\Delta}{4a}\rightarrow-\dfrac{(0+1600)}{-16}[/tex]
[tex]\sf \displaystyle y_v=-\dfrac{\Delta}{4a}\rightarrow-\dfrac{(1600)}{-16}[/tex]
[tex]\sf \displaystyle y_v=-\dfrac{\Delta}{4a}\rightarrow +100[/tex]
[tex]\boldsymbol{ \sf \displaystyle y_v = 100 }[/tex]
A soma de x +y:
[tex]\sf \displaystyle x+y = 0 + 100[/tex]
[tex]\boxed{ \boxed { \boldsymbol{ \sf \displaystyle x+ y = 100 }}} \quad \gets \text{\sf \textbf{Resposta } }[/tex]
Alternativa correta é o item D.
Explicação passo-a-passo: